The role of Ni in modifying the order of the phase transition of La(Fe, Ni, Si)13. (November 2018) - Moreno-Ramírez, Luis M.; Romero-Muñiz, Carlos; Law, Jia Yan; Franco, Victorino; Conde, Alejandro; Radulov, Iliya A.; Maccari, Fernando; Skokov, Konstantin P.; Gutfleisch, Oliver
Abstract: In this work, we study the effect of Ni substitution on the magnetocaloric properties of La(Fe, Si)13 compounds. Sample quality has been optimized by a combination of induction melting and suction casting techniques, which allowed to shorten the annealing time by an order of magnitude and expand the existing range of LaFe11.6-x Nix Si1.4 phase with cubic NaZn13 -type structure up to x = 0.4. According to our Density Functional Theory calculations, Ni addition does not significantly alter the crystal structure (finding that Ni atoms occupy preferably 96i positions) as well as the total magnetic moment; both predictions are in agreement with experimental results. With increasing of Ni concentration, the transition temperature increases and the order of the phase transition changes from first to second-order type. In addition, we show that the magnetic field dependence of magnetocaloric effect enables a clear analysis of the order of phase transition even for compositions near the critical point, surpassing the accuracy of conventionally used techniques for determining the order of magnetic phase transitions (e.g. Banerjee's criterion). Graphical abstract: Image 1